Application of chimerical ALT perforator flap with vastus lateralis muscle mass for the reconstruction of oral and submandibular defects after radical resection of tongue carcinoma: a retrospective cohort study - Rong Yang; Xiaoshan Wu; Pathak Ajit Kumar; Yafei Xiong; Canhua Jiang; Xinchun Jian; Feng Guo (BMC, 2020)
Abstract Background Patients with tongue carcinoma who undergo combined tongue and neck radical resection often have simultaneous oral and submandibular defects. Due to its high flexibility, the anterolateral thigh (ALT) perforator flap is gradually being adopted by surgeons for oral reconstruction. However, the tissue volume of perforator flaps is insufficient for the reconstruction of both the oral and submandibular regions. In this retrospective cohort study, we compared the postoperative outcomes and complications between patients reconstructed with using the classical ALT perforator flap and patients reconstructed using the chimeric ALT perforator flap with vastus lateralis muscle mass. Methods From August 2017 to August 2019, 25 patients underwent reconstructive therapy using a classical ALT perforator flap (classical group), while 26 patients were reconstructed with the chimeric ALT perforator flap (chimeric group) after radical resection of tongue cancer in Xiangya Hospital, Central South University. The flap survival rate, incidence of submandibular infection, lateral appearance, lower extremity function, and quality of life were compared between the two groups. Results There were no differences in flap survival rate and postoperative lower extremity function between the two groups. The incidence of submandibular infection was 15.4 and 40% in the chimeric and classical group, respectively. The duration of recovery was 12.20 ± 2.69 and 15.67 ± 4.09 days in the chimeric and classical group, respectively. The submandibular region fullness was satisfactory in the chimeric group. The postoperative quality of life in the chimeric group was better than that in the classical group (P < 0.05). Conclusions The chimerical ALT perforator flap with muscle mass reconstructs both the oral and submandibular defects accurately. It maintains the profile and fullness of the submandibular region and may reduce the incidence of submandibular infection.